The Maximal SINR Selection Mode for 5G Millimeter-Wave MIMO: Model Systems and Analysis - Dinh-Thuan Do; Duc-Anh Nguyen (Institute of Advanced Engineering and Science, 2017)
In mmWave massive MIMO systems, the lens antenna array and beam selection by beamspace MIMO are employed to target the number of required RF chains reduced without obvious performance loss. For cost – effective, the number of RF chain is an allowable limitation, however, to obtain the near-optimal capacity efficiently, beam selection must require the exact information of the wide size of beamspace channel. Solution to this problem, in this paper we suggest analyzing whole beamspace based on maximal SINR. More specicfically, it is confirmed that the proposed beam selection algorithms achieve higher power efficiencies than a full system where all beams are employed.